Bahaya Obesitas terhadap Perkembangan Kognitif dan Emosional Anak Usia Dini - Aisyah Amina Maryam; Ismaniar Ismaniar; Lili Dasa Putri (Journal Innovation In Education, 2025)
Obesity in early childhood has become an increasing health issue that significantly affects children’s physical, cognitive, and emotional development. This condition results from an imbalance between energy intake and physical activity and is influenced by dietary patterns, family environment, parenting, technology exposure, and biological factors. Childhood obesity disrupts not only physical health but also impacts attention, memory, focus, and emotional regulation. This study uses a literature review method by analyzing various research related to childhood obesity and its developmental effects. Findings reveal that obesity reduces brain activity, decreases learning performance, and increases risks of anxiety and low self-esteem. Prevention strategies include monitoring dietary intake, increasing physical activity, applying healthy parenting styles, and strengthening collaboration between families and educational institutions. In conclusion, obesity poses a serious threat to children’s development and requires strong parental involvement in early prevention.